Stakeholder perceptions and experiences of competency-based training with entrustable professional activities (SPECTRE): protocol of a systematic review and thematic synthesis of qualitative research - Justin Phung; Lindsay Cowley; Lindsey Sikora; Susan Humphrey-Murto; Kori A LaDonna; Claire Touchie; Roy Khalife (BMC Medical Education)
Abstract Background Competency-Based Medical Education (CBME) aims to align educational outcomes with the demands of modern healthcare. Entrustable Professional Activities (EPAs) serve as key tools for feedback and professional development within CBME. With the growing body of literature on EPAs, there is a need to synthesize existing research on stakeholders’ experiences and perceptions to enhance understanding of the implementation and impact of EPAs. In this synthesis, we will address the following research questions: How are Entrustable Professional Activities experienced and perceived by stakeholders in various healthcare settings, and what specific challenges and successes do they encounter during their implementation? Methods Using Thomas and Harden’s thematic synthesis method, we will systematically review and integrate findings from qualitative and mixed-methods research on EPAs. The process includes a purposive literature search, assessment of evidence quality, data extraction, and synthesis to combine descriptive and analytical themes. Discussion This study aims to provide insights into the use of EPAs for competency-based education, reflecting diverse contexts and viewpoints, and identifying literature gaps. The outcomes will guide curriculum and policy development, improve educational practices, and set future research directions, ultimately aligning CBME with clinical realities. Trial Registration Not required.